The translation of legal texts on the basis of Skopostheorie (in Greek) - Vlachopoulos, Stefanos (International Journal of Speech, Language and the Law, 2001)
The aim of the thesis is to examine the feasibility of translating legal textsfor different purposes (skopoi), to establish linguistically the comparativedegree of difficulty for the two combinations English–Greek andGerman–Greek and to propose a model for the teaching of specializedtranslation. The theoretical infrastructure for the first aspect is the Skopostheorie.This theory, introduced by the German scholars Reiss andVermeer, propounds a functional approach to translating, where the translatordetaches himself from the source text and prioritizes the skopos orpurpose and the effect of the translation on the final recipient.Randomly selected professional translators rendered a particularGerman lease (civil law) and a particular English lease (common law) intoGreek (civil law) for one specific skopos each. The translators did notknow that the translations would be used for research purposes. The designatedskopoi were selected on the basis of my experience as a translator.In the first skopos the translators were asked to render both the Englishand the German original for a layman with no legal knowledge; in thesecond skopos they had to translate for a comparative lawyer wishing tobecome acquainted with the formulation of leases in the legal sourcesystem, while in the third skopos the translated text was bound for aGreek court.The analyses of the way the lexicon, the syntax and the textlinguisticfeatures of the source texts were translated for each skopos revealed thatnone of the source texts were translated adequately as a whole. However,indications were found within nearly every translation that a skopos-orientedrendering of legal texts is possible. For example the common lawterm landlord was rendered into Greek by the term ekmisqwt–z (lessor),which is the one used in Greek leases (functional equivalent), and not bythe term idiokt–tjz (owner, landlord) thus depriving the comparativelawyer of the denotation of the source term. However, the translation ofthe term landlord as ekmisqwt–z was considered acceptable in the case ofthe layman recipient. Comparing the translation processes for both pairs,the higher degree of difficulty for the translation from English (commonlaw) into Greek (civil law) could be proven experimentally, since for thetransfer of meaning from one legal system into another the translator hasto consider more linguistic and legal parameters than in the translation ofthe German lease (civil law) into Greek (civil law).Finally, a model for teaching specialized translation structured aroundSkopostheorie and the feasibility of translating legal texts for differentskopoi was introduced. The manipulation of the skopos for a particulartext allows the instructor to increase gradually the difficulty of the task byasking the students to translate in the early stages for skopoi whichdemand only a minimum of effort, for example to inform a potential clientabout the content of a text. Later the task would be to translate a text forsomeone interested in the structure of the source text, but who is ignorantof the language, while the third level would be to ask the student toproduce a functionally equivalent text. That way the students graduallyacquire the necessary skills for a skopos-oriented translation and becomeaware of the limits of language and the wider meaning of the term translation.